Exploring the Influence of Perceived Usefulness and Perceived Ease of Use on Technology Engagement of Business Administration Instructors - Bancoro, Jaysone Christopher (PT FORMOSA CENDEKIA GLOBAL, 2024)
The increasing prevalence of technology in educational settings, driven by advancements in digital tools and changing pedagogical paradigms, has made its integration vital, particularly in business education, to prepare students for success in dynamic environments. The pandemic further accelerated the adoption of flexible learning modalities, emphasizing the necessity for increased adaptability and resilience in traditional learning environments, and underscoring technology's indispensable role in education. The research methodology involves a quantitative descriptive design, utilizing surveys administered to twenty-nine (29) faculty members of the Negros Oriental State University, Main Campus 1. The study used descriptive statistics and structural equation modeling. The findings indicate a strong agreement among respondents regarding the usefulness and ease of utilizing technology in teaching contexts, with mean scores reflecting high levels of agreement across various statements. Notably, instructors perceived technology as highly useful in teaching and generally find technology easy to use. However, the cognitive challenges associated with its integration are acknowledged, particularly concerning the mental effort required. The study reveals widespread adoption of technology for instructional purposes among respondents, with video conferencing, learning management systems, and collaboration platforms being the most commonly used tools. Furthermore, the analysis of the relationship between technology engagement and technology utilization suggests that perceived usefulness and ease of use do not significantly impact engagement with technology in educational settings. The recommendation is to establish technology integration committees, implement clear standards, invest in infrastructure, offer innovation incentives, foster openness to avoid technology hesitancy, integrate technology into curriculum design, facilitate online collaboration, emphasize data privacy, build community partnerships, and prioritize continuous evaluation.